Unraveling The Worldwide Pollution Haven Effect - Grether, Jean-Marie 1997- (The World Bank, 2006)
This paper contributes to the debate on the existence of pollution haven effects by systematically measuring the pollution content of trade (measured by the pollution content of imports, PCI) and decomposing it into three components-a "deep" component (unrelated to the environmental debate but including variables traditionally present in the gravity model) and two components (factor endowments and environmental policies) that occupy center stage in the debate on trade and the environment. The decomposition is carried out for 1986-88 for an extensive data set covering 10 pollutants, 48 countries, and 79 ISIC 4-digit sectors. Illustrative decompositions presented for three of the 10 pollutants in the data set indicate a significant pollution haven effect which increases the PCI of the North because of stricter environmental regulations in the North. At the same time, the factor endowment effect decreases the PCI of the North as the North is relatively well-endowed in capital and pollution-intensive activities are also capital-intensive. On a global scale, because the bulk of trade is intraregional with a high North-North share, these effects are small relative to the "deep" determinants of the worldwide pollution content of trade. In sum, although the impact has been stronger on vertical (North-South) trade flows, differences in factor endowments and environmental policies have only marginally affected the pollution content of world trade during the 1986-88 period